European COMPARative Effectiveness research on blended Depression treatment versus treatment-as-usual (E-COMPARED): study protocol for a randomized controlled, non-inferiority trial in eight European countries. Issue 1 (December 2016) - Kleiboer, Annet; Smit, Jan; Bosmans, Judith; Ruwaard, Jeroen; Andersson, Gerhard; Topooco, Naira; Berger, Thomas; Krieger, Tobias; Botella, Cristina; Baños, Rosa; Chevreul, Karine; Araya, Ricardo; et al.
Abstract Background Effective, accessible, and affordable depression treatment is of high importance considering the large personal and economic burden of depression. Internet-based treatment is considered a promising clinical and cost-effective alternative to current routine depression treatment strategies such as face-to-face psychotherapy. However, it is not clear whether research findings translate to routine clinical practice such as primary or specialized mental health care. The E-COMPARED project aims to gain knowledge on the clinical and cost-effectiveness of blended depression treatment compared to treatment-as-usual in routine care. Methods/design E-COMPARED will employ a pragmatic, multinational, randomized controlled, non-inferiority trial in eight European countries. Adults diagnosed with major depressive disorder (MDD) will be recruited in primary care (Germany, Poland, Spain, Sweden, and the United Kingdom) or specialized mental health care (France, The Netherlands, and Switzerland). Regular care for depression is compared to "blended" service delivery combining mobile and Internet technologies with face-to-face treatment in one treatment protocol. Participants will be followed up at 3, 6, and 12 months after baseline to determine clinical improvements in symptoms of depression (primary outcome: Patient Health Questionnaire-9), remission of depression, and cost-effectiveness. Main analyses will be conducted on the pooled data from the eight countries (n = 1200 in total, 150 participants in each country). Discussion The E-COMPARED project will provide mental health care stakeholders with evidence-based information and recommendations on the clinical and cost-effectiveness of blended depression treatment. Trial registration France: ClinicalTrials.govNCT02542891 . Registered on 4 September 2015; Germany: German Clinical Trials RegisterDRKS00006866 . Registered on 2 December 2014; The Netherlands: Netherlands Trials RegisterNTR4962 . Registered on 5 January 2015; Poland: ClinicalTrials.GovNCT02389660 . Registered on 18 February 2015; Spain: ClinicalTrials.govNCT02361684 . Registered on 8 January 2015; Sweden: ClinicalTrials.govNCT02449447 . Registered on 30 March 2015; Switzerland: ClinicalTrials.govNCT02410616 . Registered on 2 April 2015; United Kingdom: ISRCTN registry, ISRCTN12388725 . Registered on 20 March 2015.